Anatomical Characteristics of the Left Atrium and Left Atrial Appendage in Relation to the Risk of Stroke in Patients With Versus Without Atrial Fibrillation. (19th July 2021) - Smit, Jeff M.; Simon, Judit; El Mahdiui, Mohammed; Szaraz, Lili; van Rosendael, Philippe J.; Kolassváry, Márton; Szilveszter, Balint; Delgado, Victoria; Merkely, Béla; Maurovich-Horvat, Pál; Bax, Jeroen J.
Abstract : Background: The left atrial appendage (LAA) has been regarded as an important source of cardiac thrombus formation and appears important in the contribution to thromboembolism in patients with atrial fibrillation (AF). Our aim was to evaluate the relationship between LAA morphology and previous stroke or transient ischemic attack in 2 large and distinct patient cohorts with and without known AF. Methods: The study population consisted of patients with and without drug-refractory AF who underwent computed tomography before transcatheter AF ablation or clinically indicated for suspected coronary artery disease. The computed tomography data were used for volumetric assessment of the left atrium and LAA and to determine LAA morphology. The LAA was classified by 3 readers in consensus as chicken wing, swan, cauliflower, or windsock, based on predefined morphology classification criteria. Results: In total, 1813 patients (mean age 59±11 years, 42% female) who underwent computed tomography were included in this analysis (908 patients with AF and 905 patients without known AF). Swan LAA morphology was independently associated with prior stroke/transient ischemic attack in the overall study population (odds ratio, 3.40, P <0.001), and in patients with (odds ratio, 2.88, P =0.012) and without known AF (odds ratio, 3.96, P =0.011). Conclusions: Swan morphology of the LAA is independently associated with prior stroke or transient ischemic attack in patients with known AF, as well as in patients not previously diagnosed with AF.